Activation of neutrophils by a novel triggering immunoglobulin-like receptor MAIR-IV - 渋谷, 和子; 戸塚, 直也; 本多, 伸一郎; 中埜, 貴子; 小田, ちぐさ; 渋谷, 彰; 田原, 聡子 (Nihon Rinsho Men'eki Gakkai Sokai Shorokushu, 2009)
Myeloid cells play an important role for innate immunity against microbial infections. However, little is known about how their activation is regulated. We previously identified paired activating and inhibitory receptors, myeloid-associated immunoglobulin-like receptor (MAIR)-I and MAIR-II, preferentially expressed on myeloid cells (Yotsumoto, et al. J Exp Med, 2003, Okoshi, et al. Int Immunol, 2005, Nakahashi, et al. J Immunol, 2007). We and others have recently found that MAIR-I and MAIR-II are members of a multigene family consisting of at least 9 genes on a small segment of mouse chromosome 11. Here, we show molecular and functional characteristics of MAIR-IV, a new member of MAIR family. MAIR-IV was preferentially expressed on neutrophils in the peripheral blood, bone marrow, peritoneal cavity and spleen. MAIR-IV physically associates with immunoreceptor tyrosine based activating motif (ITAM)-bearing adaptor FcRγ chain. Cross-linking MAIR-IV with anti-MAIR-IV monoclonal antibody significantly induced secretion of proinflammatory cytokine TNF-α from neutrophils. Thus, MAIR-IV may regulate activation of neutrophils and play an important role for innate immunity.